Does the Symmetry of Patellar Morphology Matter When Matching Osteochondral Allografts for Osteochondral Defects Involving the Central Ridge of the Patella?. Issue 7 (31st July 2020) - Salka, Nabeel; Ramme, Austin; Grant, John; Scott, Jaron; Patel, Karan
Objectives: Osteochondral allografts of the patellar are currently matched solely based on tibial width. It is currently unknown whether matching by tibial width is a reasonable surrogate measurement to allow for optimum chondral surface matching or if patellar size and/or surface morphology (i.e., Wiberg classification) should be taken into account. This consideration may be especially important for chondral defects on the patellar apex. The purpose of this study was to use circumferential step-off height and chondral surface mapping to determine if differences in patellar surface morphology (i.e., Wiberg classification) play a role in the ability of donor patellar osteochondral allografts to match the native patellar surface when treating osteochondral defects involving the central ridge of the patella. The secondary purpose was to explore the relationship between tibial width and patellar size (width and height) to determine if tibial width strongly related to patellar size to allow it to act as a surrogate measure for patellar size. Methods: Twenty (10 Wiberg I and 10 Wiberg II/III) fresh frozen patellae were designated as the recipient. Each recipient was size-matched (within ± 2mm tibial width) to both a Wiberg I and a Wiberg II/III patellar donor to produce 20 size-matched trios. All patellas were classified as Wiberg I, II, or III by visual inspection. The patellar height and widths were also measured. The recipient patella underwent initial nanoCT scanning to quantify the native chondral surface morphology. A 16mm circular osteochondral "defect" centered on the central ridge of the patella was then created in the recipient patella. Within each set of three patellae, the donor Wiberg I and Wiberg II/III patellae were randomly assigned, using a random number generator, to be transplanted first or second. The randomly ordered donor Wiberg I or Wiberg II/III plug was harvested from a homologous location and transplanted into the recipient. The recipient was then nano-CT scanned, digitally reconstructed, registered to the initial nano-CT scan of the recipient patella. It was then processed in Dragon Fly to determine circumferential step-off heights between the native and donor surfaces at three degree intervals. This was calculated for the entire circumference and for each quadrant (superior, medial, inferior, lateral) to determine if the ste-off heights varied by locations. MATLAB was used to determine the height deviation (dRMS) between the native and donor surfaces at over 3000 surface points (Figure 1). The initial transplant was carefully removed and the process was then repeated for the other donor allograft. Pearson correlation coefficient, 2-way ANOVA with Tukey's multiple comparison, and paired t-tests were used when appropriate. Sample size of 10 trios was determined based on previous work in our lab (clinically relevant difference of 0.75mm, SD = 0.5mm, α = 0.05, power 0.8; 7 samples per group). Results: There was no significant difference in mean step-off heights between matched and unmatched Wiberg allograft plugs (Table 1). When analyzing all patellas, the superior (p = 0.01) and lateral (p = 0.001) quadrants demonstrated step-off heights that were significantly greater compared to the inferior quadrant, however these findings were not clinically significant. There was a statistically significant difference in height deviation over the whole surface between native and donor plugs when comparing matched and unmatched Wiberg plugs (p=0.049), however this finding was not clinically significant (Table 2). There was no difference across individual quadrants. There was a linear correlation when comparing tibial width to patellar width (r = 0.82) and patellar height (r = 0.68). Conclusions: Differences in Wiberg classification did not lead to clinically relevant differences in step-off height or surface height deviations for the whole donor plug or by quadrant. Tibial width is a reasonable measure to predict patellar size (width and height). It is therefore reasonable to continue matching osteochondral allografts of the patella based on the easy to measure value of tibial width without consideration for patellar size or Wiberg classification. Table 1. Mean ± SD step-off height measurements (in mm) for the medial, lateral, superior, and inferior quadrants, and whole patella for matched (n = 20), unmatched (n = 20), and all (n = 40) patallas. Note that all patellas superior and lateral was statistically different than inferior (*0=0.01 + 0=0.001) Circumferential Step-Off Height Matched Wiberg (n=20) Unmatched Wiberg (n=20) All Patellas (n=40) Medial 0.44 ± 0.21 0.57 ± 0.35 0.51 ± 0.30 Lateral 0.54 ± 0.20 0.66 ± 0.42 0.60 ± 0.33* Superior 0.57 ± 0.23 0.55 ± 0.21 0.56 ± 0.22 + Inferior 0.32 ± 0.17 0.41 ± 0.19 0.36 ± 0.18 Total 0.55 ± 0.18 0.60 ± 0.26 0.57 ± 0.22 Table 2. Mean ± SD surface deviation (in mm) for medial, lateral, superior, and inferior quadrants, and whole patella for matched (n =20) and unmatched (n = 20) Wiberg donor transplants Circumferential Step-Off Height Matched Wiberg (n=20) Unmatched Wiberg (n=20) P Medial 0.48 ± 0.20 0.51 ± 0.26 0.994 Lateral 0.42 ± 0.24 0.49 ± 0.22 0.889 Superior 0.48 ± 0.23 0.59 ± 0.30 0.576 Inferior 0.43 ± 0.24 0.58 ± 0.35 0.262 Total 0.50 ± 0.14 0.64 ± 0.25 0.049